Pendampingan Teknis Perencanaan Renovasi Pembangunan Masjid As-Syuhada Rumpun Diponegoro Kota Semarang - Sri Wanto; Hendra Masvika; Lila Anggraini; Trias Widorini; Annisa Zahrotun Na'imah (Universitas Semarang, 2023)
Mosques are one the public facilities that have a role as houses of worship for muslims. In addition, the mosque also functions as a center for community activities such as a place for celebrating big days, discussions, studies, seminars, lectures, and training as a center for religious learning for the community. To increase the role and function of the mosque as well as an effort to increase the capacity or capacity of worshippers, the mosque prosperity council (DKM) plans to renovate the construction of mosque. The existing condition of the mosque currently has supporting facilities, but it is considered inadequate with a limited capacity of worshippers. In addition, physically the existing mosque building is quite simple, so carrying out renovations requires careful planning. The purpose of this community service (PkM) of Faculty of Engineering of Universitas Semarang is to assist DKM in making a renovation plan design for the construction of the As-Syuhada Mosque. The output of this mentoring activity is in the form of submitting design drawings of the 2 floors mosque building including detailed structural drawings, as well as 3D drawings and calculation of the cost budget plan (RAB). The drawings and RAB of the renovation work for the construction of the As-Shahada Mosque that had been approved were then used as guidelines for carrying out work in the field.